2021
DOI: 10.3390/ijms221910417
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Biomarkers of Transition from Metabolically Healthy Obesity to Metabolically Unhealthy Obesity Phenotype: A Prospective Study

Abstract: Background: Identifying those parameters that could potentially predict the deterioration of metabolically healthy phenotype is a matter of debate. In this field, epigenetics, in particular DNA methylation deserves special attention. Results: The aim of the present study was to analyze the long-term evolution of methylation patterns in a subset of metabolically healthy subjects in order to search for epigenetic markers that could predict the progression to an unhealthy state. Twenty-six CpG sites were signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 44 publications
(43 reference statements)
1
10
0
Order By: Relevance
“…7 Recently, our group identified in a prospective study two differentially methylated positions located in the ZFPM2 and CYP2E1 genes, closely associated with the transition from MHO to MUO state. 8 A recent metaanalysis conducted by Andrade et al (2021) found more than 2000 DMRs in the adipose tissue of individuals with MUO compared to individuals with MHO, as our study reported. 14 There are several genes that overlapped our DMRs, such as FLRT, FRMPD4 PSMD5, NKX or LRRC, suggesting a similar effect in obesity.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…7 Recently, our group identified in a prospective study two differentially methylated positions located in the ZFPM2 and CYP2E1 genes, closely associated with the transition from MHO to MUO state. 8 A recent metaanalysis conducted by Andrade et al (2021) found more than 2000 DMRs in the adipose tissue of individuals with MUO compared to individuals with MHO, as our study reported. 14 There are several genes that overlapped our DMRs, such as FLRT, FRMPD4 PSMD5, NKX or LRRC, suggesting a similar effect in obesity.…”
Section: Discussionsupporting
confidence: 74%
“…A prospective study carried out by Gallardo‐Escribano et al (2020) reported that several metabolic genes ( LPL , SCD , SREBF1 , LXR ) were epigenetically altered in the MHO group after 12 months of follow‐up 7 . Recently, our group identified in a prospective study two differentially methylated positions located in the ZFPM2 and CYP2E1 genes, closely associated with the transition from MHO to MUO state 8 . A recent meta‐analysis conducted by Andrade et al (2021) found more than 2000 DMRs in the adipose tissue of individuals with MUO compared to individuals with MHO, as our study reported 14 …”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…Here, we focus on its functions in immune and metabolic systems, which may commonly impact psoriasis and AD through peripheral blood. Previous clinical trials implicated that hypermethylated ZFPM2 protects against the occurrence and progression of metabolic complications in obesity and could affect immunity-related pathways ( 56 ). Meanwhile, some research implicated that decreasing ZFPM2 enhances insulin sensitivity via upregulating PPARA expression ( 57 , 58 ).…”
Section: Discussionmentioning
confidence: 99%